EUROSOI-ULIS 2015: 2015 Joint International EUROSOI Workshop and International Conference on Ultimate Integration on Silicon 2015
DOI: 10.1109/ulis.2015.7063777
|View full text |Cite
|
Sign up to set email alerts
|

Spectral sensitivity of a graphene/silicon pn-junction photodetector

Abstract: We investigate the optical properties of graphenesilicon Schottky barrier diodes composed of chemical vapor deposited (CVD) graphene on n-and p-type silicon (Si) substrates. The diodes fabricated on n-Si substrate exhibit better rectifying behavior compared to p-Si devices in the dark. An ultra-broadband spectral response is achieved for n-Si diodes. The results are compared with the spectral response of a molybdenum disulfide (MoS 2 ) -p-type silicon photodiode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…State-of-the-art bulk semiconductor PDs achieve values in the range of n = 1-2. We reported large area graphene/Si Schottky diodes by transferring large-area (2ˆ4 cm 2 ) single-layer CVD-grown graphene onto n-type Si (Figure 1c, black solid line) [57], demonstrating the integration of 2D materials into the existing Si platform. The simple, yet scalable fabrication process yielded devices with peak sensitivity of 270 mAW´1 at 992 nm and an ideality factor of approximately 1.5.…”
Section: Graphene Photodetectorsmentioning
confidence: 94%
See 1 more Smart Citation
“…State-of-the-art bulk semiconductor PDs achieve values in the range of n = 1-2. We reported large area graphene/Si Schottky diodes by transferring large-area (2ˆ4 cm 2 ) single-layer CVD-grown graphene onto n-type Si (Figure 1c, black solid line) [57], demonstrating the integration of 2D materials into the existing Si platform. The simple, yet scalable fabrication process yielded devices with peak sensitivity of 270 mAW´1 at 992 nm and an ideality factor of approximately 1.5.…”
Section: Graphene Photodetectorsmentioning
confidence: 94%
“…Vertical p-n junctions can be fabricated by stacking 2D materials on bulk materials or on other 2D materials, similar to the graphene/Si devices described in Section 4.1 [57]. While Lopez-Sanchez et al investigated exfoliated MoS 2 flakes on Si [84], Yim et al demonstrated the fabrication of large-area CVD MoS 2 /Si devices, where a sputtered Mo film was sulfurized in a highly controllable and reproducible manufacturing process [85].…”
Section: Tmd Photodetectorsmentioning
confidence: 99%
“…Another interesting stacked photodetector structure is based on 2D material combined with other traditional p-type semiconductors, such as p-Si, p-Ge and p-GaN [105,148]. Several researches are based on pn-diode photodetectors of CVD graphene/Si and CVD TMDC/Si and show excellent optical response [149][150][151]. For example, An et al reported a tunable graphene/p-Si heterojunction photodetector in the frequency of MHz [150].…”
Section: Junction Type Photodetectorsmentioning
confidence: 99%
“…However, the investigation of out-of-plane electron transport across graphene is still at an early stage [5], [6], and an adequate understanding of the physical mechanisms occurring at the interfaces is still missing, also due to the poor performance of GBTs fabricated so far [7], [8] graphene are limited to Schottky-like heterostructures with different semiconductors, including Si [9], [10] and III-Nitrides [11]. Previous simulation works on GBHTs [4], [12] were mainly oriented to explore the ultimate performance of this new device concept, and assumed transparent graphene.…”
Section: Introductionmentioning
confidence: 99%
“…The base voltage V BE modulates the barrier height, and hence controls the current flow in the active region. [9] and squares [10]) and simulated with ideal (empty green symbols) and fitted (solid blue) interface model. Right: Experimental and simulated current-voltage-temperature characteristics of the diodes from [9].…”
Section: Introductionmentioning
confidence: 99%